An evaluation on the antimicrobical properties of two disinfectants on dental high-speed instruments - Nejatidanesh F; Tavakoli A; Haratian A (Tehran University of Medical Sciences, 2003)
Statement of Problem: Rotary dental instruments (i-e. iow speed and high speed handpieces), due to"ninfection spread high potentiality, should be sterilized between dental visits for each patient. When a high"nspeed rotary instrument pauses at a high velocity, contaminated fluids like blood and saliva will be"nsucked into its tubes."nPurpose: The aim of this study was to compare the bactericidal effects ofDeconex 53 plus solution and"nthe solarsept spray on dental high- speed instruments."nMaterials and Methods: In this experimental study, one hundred and twenty (120) dental high- speed"nturbines, sterilized by autoclave, were divided into 6 groups. The turbines were contaminated with"nbacterial suspension. Streptococcus mutans, Staphilococcus aureus and Neisseria SP were the first"nmicrobial groups. Pseudomonas aruginosa was the second microbial group and Bacillus subtilis spore"nwas the third microbial group. After 5 minutes, three contaminated groups were placed in Deconex53"nplus 2% solution for 15 minutes. Three other groups after contamination were sprayed with Deconex"nsoiar sept spray for 2 minutes. Then the samples were placed in TSB culture and after 24 hours"nincubation at 37°, the samples were transmitted on blood agar solid culture for bacterial viability"nobservation. The results were observed after 24 hours incubation. Proportional test with normal"ndistribution was used for data analysis."nResults: The Deconex 53 plus had 85% disinfectant activity on the first microbial group, 10% on the"nsecond microbial group and 100% on the third microbial group. Also the solarsept spray had 30%"ndisinfectant activity on the first microbial group and 15% on the third micribial group . The solarsept"nspray had no bactericidal effect on turbines contaminated by the second microbial group. The results"nproved that the disinfectant effects of Deconex 53 plus solution for 15 minutes were significantly better"nthan the solarsept spray for 10 minutes. The Deconex solution and the solarsept spray showed 65% and"n15% negative growth, respectively. Based on the elimination of all spores, Deconex 53 plus has great"nsporcidal activity."nConclusion: These disinfectants should not be considered as suitable substitutes for sterilization with"nautoclave.